New Custom Primers for the Detection of SARS-CoV-2 using the Singleplex rRT‒PCR SYBR Green-Based Method with the NSP10 and N genes as Targets - Gaffar, Shabarni; Shabrinna, Hanif; Putri, Rafika; Wiraswati, Hesti Lina; Hartati, Yeni Wahyuni; Ishmayana, Safri; Faridah, Lia; Ekawardhani, Savira (Departemen Kimia, 2025)
Although COVID-19 is no longer a global health emergency, rapid, sensitive, and specific detection tests are still needed. In this study, we developed a cost-effective test, the SYBR Green-based rRT‒PCR kit, using new custom primers targeting the N and NSP10 genes of the SARS-CoV-2 virus. The specificity of the designed primers was determined through agarose gel electrophoresis. A standard curve generated from a ten-fold dilution of SARS-CoV-2 RNA was used to determine the efficiency and sensitivity of the kit. Validation of this protocol was carried out on ten clinical specimens. As expected, the results showed that the N and NSP10 gene primers produced 134 and 161 bp products, respectively. The limits of detection and limit of quantification with N gene primers were 7.74 and 23.46 copies/μL, respectively, and those with the NSP10 gene primers were 4.69 and 14.21 copies/μL, with a PCR efficiency of 102.5% and 110.6%, respectively. The validation results with clinical specimens revealed that seven samples were true-positive for COVID-19 (Ct range 15.09–21.33), and three were confirmed to be true-negative. Costs associated with COVID-19 patient testing can be anticipated to decrease with the use of custom primers for the detection of SARS-CoV-2 via the use of the singleplex rRT‒PCR mix SYBR Green.